2018
DOI: 10.1177/1744987117748348
|View full text |Cite
|
Sign up to set email alerts
|

Building clinical academic leadership capacity: sustainability through partnership

Abstract: A national clinical academic training programme has been developed in England for nurses, midwives and allied health professionals but is insufficient to build a critical mass to have a significant impact on improved patient care. We describe a partnership model led by the University of Southampton, and its neighbouring National Health Service (NHS) partners that has the potential to address this capacity gap. In Key to the success of our partnership model is the strength of the strategic relationship develope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
81
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(82 citation statements)
references
References 4 publications
1
81
0
Order By: Relevance
“…There is a long tradition of doctors and dentists pursuing academic research alongside their clinical practice 1. However, it is increasingly acknowledged that nurses, midwives and allied health professionals (AHPs) (henceforth NMAHPs) are also well-placed to devise solutions to the problems that they observe first hand in their day-to-day clinical practice 2.…”
Section: Introductionmentioning
confidence: 99%
“…There is a long tradition of doctors and dentists pursuing academic research alongside their clinical practice 1. However, it is increasingly acknowledged that nurses, midwives and allied health professionals (AHPs) (henceforth NMAHPs) are also well-placed to devise solutions to the problems that they observe first hand in their day-to-day clinical practice 2.…”
Section: Introductionmentioning
confidence: 99%
“…Recent literature shows that there are already several successful programme models which have been developed between NHS and HEI organisations intended to support integration of more NMAHP clinical academic roles to expand research capacity in NHS practice (Westwood et al, 2018), including the NIHR Integrated Clinical Academic programme Programme (Health Education England/National Institute for Health Research, 2019). However, these are typically hosted and situated within larger university hospital organisations and, while linked to practice, are primarily focused on an academic research model (Strickland, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…These roles are long established in the medical profession with a developing focus across nursing, midwifery and allied health professionals (NMAHPs) (Carrick-Sen et al, 2016;Strickland, 2017). However, as Westwood et al (2018) highlight, although there is a national clinical academic training scheme in England focusing on the NMAHP workforce, it currently lacks the capacity to build the level of clinical academic leadership needed for the scale of innovation and improvements required across NHS health care.…”
Section: Introductionmentioning
confidence: 99%
“…Research capacity-building initiatives have also been proposed in other sectors. In the health sciences, research infrastructure development challenges have been identified in regard to public health, medicine, and nursing (Brownson, Fielding, & Green, 2018;Westwood, Richardson, Latter, Clark, & Fader, 2018). Similar efforts have been noted in adjacent professions including business, public administration, and public policy (Bartunek & Rynes, 2014;George, Howard-Grenville, Joshi, & Tihanyi, 2016;Paton, Chia, & Burt, 2014).…”
mentioning
confidence: 79%